Autonomous orbit determination for formations of Cubesats beyond LEO. (December 2018) - Vasile, Massimiliano; Torre, Francesco; Serra, Romain; Grey, Stuart
Abstract: This paper investigates the use of the Time Of Arrival (TOA) and Doppler shift to allow a small formation of CubeSats to navigate beyond low Earth orbit (LEO). The idea is to use a one way communication, from one or more ground stations to two or more CubeSats, to reconstruct an estimation of the position and velocity of the formation with respect to Earth. The paper considers the use of the difference in TOA and Doppler measurements to mitigate the error introduced by the onboard clock. These measurements are combined with inter-satellite distance and velocity measurements based on a two-way communication between pairs of spacecraft. The paper will provide an estimation of the error in position and velocity that can be obtained by a combination of these measurements. The reference case for these analyses will be a transfer trajectory to the Moon.